2023
DOI: 10.3389/fnins.2023.1197733
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating or disturbing? An investigation about the effects of auditory frequencies on prefrontal cortex activation and postural sway

Abstract: Auditory stimulation activates brain areas associated with higher cognitive processes, like the prefrontal cortex (PFC), and plays a role in postural control regulation. However, the effects of specific frequency stimuli on upright posture maintenance and PFC activation patterns remain unknown. Therefore, the study aims at filling this gap. Twenty healthy adults performed static double- and single-leg stance tasks of 60s each under four auditory conditions: 500, 1000, 1500, and 2000 Hz, binaurally delivered th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Lower resources are instead dedicated to PVT execution, leading to a decrease in performance, as highlighted by the increase in RT. As a matter of fact, previous studies have pointed out that, when the vestibular system is challenged, maintaining the same balance and posture starts to be cognitively demanding [1,2,66]. However, on the other hand, the incorporation of vestibular stimulation, like swinging on a swing during leisure time, as suggested in [67], over time could instead improve cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…Lower resources are instead dedicated to PVT execution, leading to a decrease in performance, as highlighted by the increase in RT. As a matter of fact, previous studies have pointed out that, when the vestibular system is challenged, maintaining the same balance and posture starts to be cognitively demanding [1,2,66]. However, on the other hand, the incorporation of vestibular stimulation, like swinging on a swing during leisure time, as suggested in [67], over time could instead improve cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…Authors outlined how visual-vestibular interactions enhance postural stability by interpreting the head's position and generating eye movements accordingly, which helps differentiate self-motion or external motion and achieve gaze stabilization and postural control. Indirect measurement of brain responses to postural changes is also addressed through the assessment of neuromuscular and motor functions, as in the investigation of defense mechanisms adopted to keep the body away from the stimulus (Graziano and Cooke, 2006 ; Belluscio et al, 2023 ). In humans the space directly surrounding the body at a grasping distance has been depicted as defensive peripersonal space for tactile (Rizzolatti et al, 1997 ) or auditory stimulation (Ladavas et al, 2001 ), closer the stimulation to the head stronger behavioral response was found (Versace et al, 2019 ).…”
Section: Postural Control and The Neuro-muscular Investigationmentioning
confidence: 99%
“…Specifically, we used a C minor pentatonic scale (C3, Eb3, F3, G3, Bb3, C4) because minor music tends to be perceived as less arousing, more contemplative, and sadder ( Parncutt, 2014 ). Furthermore, the scale was chosen in the middle-low register (C3–C4), avoiding high-pitch tones that are mostly associated with alarm, tension, and arousal ( McAdams et al, 2017 ; Belluscio et al, 2023 ). In fact, high-pitch tones are frequently used to alarm and capture attention (e.g., Straughn et al, 2009 ; Belluscio et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the scale was chosen in the middle-low register (C3–C4), avoiding high-pitch tones that are mostly associated with alarm, tension, and arousal ( McAdams et al, 2017 ; Belluscio et al, 2023 ). In fact, high-pitch tones are frequently used to alarm and capture attention (e.g., Straughn et al, 2009 ; Belluscio et al, 2023 ). To keep the timbre as simple as possible pure tones were used.…”
Section: Introductionmentioning
confidence: 99%